2019
DOI: 10.1002/pra2.5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of domestic and cross‐country impact of Chinese and U.S. publications in chemistry

Abstract: Based on publications in Chemistry in 2015, this paper investigated the citation impact on domestic and foreign scholarly communities of Chinese and US publications, and to what extent does such impact relate to international collaboration and government funding. First‐ or corresponding authorship in international collaboration is defined as dominance and is taken into consideration. Citations to publications are designated as domestic citations (Chinese or US citations), partner citations or other citations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They found that all countries are more likely to cite other papers from the same country, yet publications from the United States are cited by researchers from all countries. Similarly, Cai et al (2019) compared the research impact between China and the United States in Chemistry. They discovered that China's publications mainly benefit from other domestic research, whereas publications from the United States have more depth and breadth of influence throughout the world.…”
Section: Related Workmentioning
confidence: 99%
“…They found that all countries are more likely to cite other papers from the same country, yet publications from the United States are cited by researchers from all countries. Similarly, Cai et al (2019) compared the research impact between China and the United States in Chemistry. They discovered that China's publications mainly benefit from other domestic research, whereas publications from the United States have more depth and breadth of influence throughout the world.…”
Section: Related Workmentioning
confidence: 99%